Understanding the Meaningfulness of Vocal and Instrumental Music Teachers' Hand Gestures Through the Teacher Behavior and Gesture Framework - Simones, Lilian (Frontiers in Education, 2019)
This article considers the usefulness of the recently proposed ‘Teacher Behaviour and Gesture (TBG) framework’ for understanding the meaningfulness of teachers’ hand gestures from an Enactive Cognition perspective (wherein cognition is fundamentally considered as embodied, embedded, enactive and extended). The framework is based on the main premise that gestures are part of an integral musical communicational process, fully integrated with speech and/or music-making and contextualised within specific teaching behaviours. By considering teachers’ teaching behaviours, it is possible to realise teachers’ pedagogical intentions. This, in turn, enables deeper understandings on teachers’ gestures from the points of view of meaning, function and purpose. Application of the TBG framework across instrumental and vocal music pedagogical contexts (one-to-one, small and large teaching groups) will bring relevant insights on developing practical scaffolding approaches, with direct implications on the quality of teaching and learning, for the benefit of both teachers and students.